FOREIGN EXPERIENCE OF THE USE OF "MINECRAFT: EDUCATION EDITION" IN PROJECT ACTIVITY - Konevshchynska О. Е. (Journal of Information Technologies in Education (ITE), 2017)
The relevance of the rapid development of Internet technologies in today’s digital society, causing rapid changes in education is substantiated in the article. A thorough analysis of the foreign experience of using the educational version of "MINECRAFT: EDUCATION EDITION" in the project activity has been carried out. Internet sources, psychological-pedagogical and educational-methodical literature on the research problem are analyzed. The main educational trends, including remote and mobile learning, MOOC, supplemented reality, cloud LMS, personalization, BigData, gamification, which change the content of education and its impact on quality are named. It is proved that the use of gaming models and techniques for educational purposes can have a positive effect on the effectiveness of children teaching. The content of the sections and the main directions of using the educational platform in the educational process and the project activity of the students and teachers are considered. The results of joint work of children in mathematics, language and literature, history and geography are presented. The important aspects that are necessary in the information society are the cooperation, self-study and effective communication of subjects of the educational process for the implementation of project-oriented, educational-cognitive and innovative activities in educational practice. A promising area for further research is the design of Minecraft: Education Edition game scenarios methodology for the further implementation in domestic educational practice.